Psychosocial impact and stigma on men who have sex with men due to monkeypox - Linares-Navarro, Rubén; Sanz-Muñoz, Iván; Onecha-Vallejo, Víctor; Fernández-Espinilla, Virginia; Eiros, Jose M.; Castrodeza-Sanz, Javier; Prada-García, Camino (Frontiers in Public Health, 2025)
BackgroundThe recent Monkeypox (Mpox) outbreak has disproportionately affected men who have sex with men (MSM), amplifying stigma and discrimination. While prior research examined media portrayals and public perceptions, little is known about MSM’s direct experiences. To address this gap, we assess discrimination, stigma, and psychosocial impact across social and healthcare settings.MethodsA cross-sectional observational study was conducted using a structured, pilot-tested survey to assess discrimination against MSM in media, family, socio-occupational, and healthcare environments.ResultsAmong 115 MSM surveyed, 81.7% observed discriminatory comments in media, while discrimination was noted in workplaces (41.7%), by family/friends (45.2%), cohabitants (15.7%), and healthcare (34.8%). Stigma significantly impacted healthcare-seeking behavior, with 33% avoiding medical care due to fear of discrimination. Psychologically, 50.4% reported low mood/anxiety, and 72.7% of those frequently fearing Mpox also experienced these symptoms. The outbreak led 71.3% to alter sexual behavior, primarily reducing encounters (60%). Fear of Mpox was strongly associated with behavioral changes (p < 0.001).ConclusionThe Mpox outbreak has exacerbated stigma toward MSM, highlighting an urgent need for intervention. Authorities, media, and community leaders must disseminate accurate information and implement psychological support programs to mitigate stigma and its detrimental effects on MSM.